Improved estimates of global terrestrial photosynthesis using information on leaf chlorophyll content. (10th April 2019) - Luo, Xiangzhong; Croft, Holly; Chen, Jing M.; He, Liming; Keenan, Trevor F.
Abstract: The terrestrial biosphere plays a critical role in mitigating climate change by absorbing anthropogenic CO2 emissions through photosynthesis. The rate of photosynthesis is determined jointly by environmental variables and the intrinsic photosynthetic capacity of plants (i.e. maximum carboxylation rate; V c max 25 ). A lack of an effective means to derive spatially and temporally explicit V c max 25 has long hampered efforts towards estimating global photosynthesis accurately. Recent work suggests that leaf chlorophyll content (Chlleaf ) is strongly related to V c max 25, since Chlleaf and V c max 25 are both correlated with photosynthetic nitrogen content. We used medium resolution satellite images to derive spatially and temporally explicit Chlleaf, which we then used to parameterize V c max 25 within a terrestrial biosphere model. Modelled photosynthesis estimates were evaluated against measured photosynthesis at 124 eddy covariance sites. The inclusion of Chlleaf in a terrestrial biosphere model improved the spatial and temporal variability of photosynthesis estimates, reducing biases at eddy covariance sites by 8% on average, with the largest improvements occurring for croplands (21% bias reduction) and deciduous forests (15% bias reduction). At the global scale, the inclusion of Chlleaf reduced terrestrial photosynthesis estimates by 9 PgC/year and improved the correlations with a reconstructed solar‐induced fluorescence product and a gridded photosynthesis product upscaled from tower measurements. We found positive impacts of Chlleaf on modelled photosynthesis for deciduous forests, croplands, grasslands, savannas and wetlands, but mixed impacts for shrublands and evergreen broadleaf forests and negative impacts for evergreen needleleaf forests and mixed forests. Our results highlight the potential of Chlleaf to reduce the uncertainty of global photosynthesis but identify challenges for incorporating Chlleaf in future terrestrial biosphere models. Abstract : We used satellite‐derived leaf chlorophyll content (Chlleaf ) to infer leaf photosynthetic capacity ( V c max 25 ) that varies temporally and spatially. The new Chlleaf ‐based V c max 25 data set was then incorporated into an established terrestrial biosphere model (i.e. BEPS) to estimate global photosynthesis. Our results show that Chlleaf ‐based V c max 25 and its seasonally average values (Chlavg ‐based V c max 25 ) can both effectively improve the estimates of photosynthesis when validated against observations at 124 sites of different plant functional types across the globe. This study highlights that Chlleaf is a valuable leaf physiological trait to add in future models to better simulate the terrestrial carbon cycle.